PENGELOLAAN PEMBELAJARAN BERDIFERENSIASI BAGI ANAK USIA DINI DI TK DHARMAWANITA BATANGSAREN 1 TULUNGAGUNG - Nabila, Yasmin; Mushlih, Ahmad (MURANGKALIH: Jurnal Pendidikan Anak Usia Dini, 2023)
Learning management is an effort to organize and control learning activities based on learning concepts and principles to succeed learning objectives to be achieved more effectively, efficiently and productively. This research is a descriptive, qualitative research, with data display analysis, data presentation, and data verification or conclusions. The data collection technique is through observation and interviews. This research covers the parts of early childhood learning management, starting from, designed, implemented, supervised, evaluated and reported learning outcomes well. This research uses a qualitative descriptive method, namely research that describes and examines the real condition of the research object based on authentic data so that it can describe in full the parts of the management of institutions in TK Dharma Wanita Batangsaren 1. The results of this study show that learning management in Dharma Wanita Batangsaren 1 Kindergarten has been well prepared. This can be seen the parts of learning management in accordance with the provisions. So that learning activities at Dharma Wanita Batangsaren 1 Kindergarten can achieve developmental aspects in accordance with the guidelines and characteristics of children aged 5-6 years.